Implementation of a quality-focused organisational structure through shop floor management - Usamah, Shamsuddin (2017)
Shop floor management is widely regarded to be a pre-requisite condition and enabler for sustainable implementation of lean processes. This thesis deals with the investigative research for the implementation of a quality-focused organisational structure in a production line through shop floor management, aimed at increasing quality and process stability. The existing structure of shop floor management currently being used in Mercedes-Benz Malaysia's Production Plant, specifically the C-Class passenger car production line, is firstly analysed to understand the dynamics and synergy of the system. The objective of this thesis is to help improve the existing shop floor management structure by further incorporating and integrating the role of station leaders with the whole production line organisation. The thesis describes the development of tools used to enforce said role which will affect significant key performance indicators in production, namely Defects per Hundred and First Time Right Rate.